2023
DOI: 10.3390/brainsci14010009
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation (tDCS) Effects on Quantitative Sensory Testing (QST) and Nociceptive Processing in Healthy Subjects: A Systematic Review and Meta-Analysis

Francisco Gurdiel-Álvarez,
Yeray González-Zamorano,
Sergio Lerma-Lara
et al.

Abstract: Background: The aim of this study is to determine the effect that different tDCS protocols have on pain processing in healthy people, assessed using quantitative sensory tests (QST) and evoked pain intensity. Methods: We systematically searched in EMBASE, CINAHL, PubMed, PEDro, PsycInfo, and Web of Science. Articles on tDCS on a healthy population and regarding QST, such as pressure pain thresholds (PPT), heat pain thresholds (HPT), cold pain threshold (CPT), or evoked pain intensity were selected. Quality was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…If the SDT of the difference was not provided, it was inferred from other data mentioned in the study: (1) utilizing other metrics reported in the study (for instance, confidence intervals and p -values, adhering to the principles outlined in Chapter 6.5.2.2 of the Cochrane Handbook) ( 17 ); or, if this was unattainable; (2) employing the correlation coefficient of the most analogous study included (adhering to the principles outlined in Chapter 6.5.2.8 of the Cochrane Handbook) ( 17 ); or if that was unattainable; (3) utilizing a conservative correlation coefficient of 0.5 ( 18 ). This methodology has been implemented in other meta-analyses ( 19 , 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…If the SDT of the difference was not provided, it was inferred from other data mentioned in the study: (1) utilizing other metrics reported in the study (for instance, confidence intervals and p -values, adhering to the principles outlined in Chapter 6.5.2.2 of the Cochrane Handbook) ( 17 ); or, if this was unattainable; (2) employing the correlation coefficient of the most analogous study included (adhering to the principles outlined in Chapter 6.5.2.8 of the Cochrane Handbook) ( 17 ); or if that was unattainable; (3) utilizing a conservative correlation coefficient of 0.5 ( 18 ). This methodology has been implemented in other meta-analyses ( 19 , 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the absence of SD of the difference, we imputed from other data reported in the study: (1) using other measures reported in the study (e.g., confidence intervals and p values, following the principles described in Chapter 6.5.2.2 of the Cochrane Handbook) ( Higgins et al, 2023 ); or, if that was not possible, (2) using the correlation coefficient of the most similar study included (following the principles described in Chapter 6.5.2.8 of the Cochrane Handbook) ( Higgins et al, 2023 ); or if that was not possible, (3) using a conservative correlation coefficient of 0.5 ( Deeks et al, 2022 ). This methodology has been performed in other meta-analyses ( Gurdiel-Álvarez et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%